ANNELID TEREBELLINA MACKAYI (BATHER) FROM MIDDLE TRIASSIC KESKAIN FORMATION, MISOOL ARCHIPELAGO, WEST IRIAN JAYA - Fauzie Hasibuan (Pusat Survei Geologi, 2007)
Terebellina mackayi is an annelid fossil species which forms a tubular agglutinated body. It is a Middle Triassic taxon which has a common distribution in the world and has been recorded from Sumatera, Thailand, Misool, Timor, and New Zealand. A collection of small sized specimens of the species from the Keskain Formation (Misool) of Anisian to Ladinian age is here redescribed and a global correlation is attempted. Terebellina mackayi is commonly found in a random orientation of distribution within beds. The organism which is constructed of tubular shape remains enigmatic but was probably suspension feeder rather than browser, deposit feeder or active predator. Terebellina mackayi lived in a fine grained black silt substrate (infauna) rich in organic detritus.Â Keywords: Keskain Formation, Annelid, Terebellina mackayi, Anisian, Ladinian